Self-reported hypersensitivity to exotic fruit in birch pollen-allergic patients - Nils E. Eriksson; Sonja Werner; Tony Foucard; Christian Möller; Torsten Berg; Jaak Kiviloog; Kerstin Norrlind; Margareta Söderberg; Jan-Åke Wihl (Allergology International, 2003)
Background: The majority of Swedish birch pollen (BP)-allergic patients report hypersensitivity to some fruits, nuts and vegetables. Some BP-allergic patients complain ‘I can’t tolerate any fruit’. The main aim of the present study was to answer the question, ‘can BP-allergic patients tolerate some of the exotic fruit, not at present common in Sweden?’ Methods: Consecutive patients (n = 397) visiting the participating Allergy Clinics, who had a BP allergy and reported a food hypersensitivity, were asked to fill out questionnaires regarding 66 different fruits and vegetables. Subjects had three alternatives as an answer to each of the food questions: (i) ‘I tolerate it’; (ii) ‘I get symptoms from it’; or (iii) ‘I have not tried this food’. Skin prick tests were performed with pollen allergens. Results: Most patients had experienced reactions to several foods; only 31 patients (8%) reported hypersensitivity to one food only. Some of the fruit had been tried by only a few patients. In addition to earlier well- known BP-related foods, more than 40% of patients who had knowingly eaten Japanese pear and pomegranate said that they had experienced symptoms after eating the fruit. Most patients tolerated pineapple, melon, grapes and citrus fruits, as well as zucchini, lychee, rambutan, mangosteen, ugli, melon pear and cherimoya. Conclusions: Although an allergy to fruit is common among BP-allergic patients, there are several widely available fruits that most patients tolerate; for instance, pineapple, melon, grapes and citrus fruit. Furthermore, there are many exotic fruits that most patients have not yet tried.